Ciutat i arquitectura en l'obra de Francesc Eiximenis. Una aproximació. - SERRA DESFILIS, AMADEO (Scripta)
Francesc Eiximenis (c. 1330-1409) is well known as an author who praised city as the best example of human community. The Franciscan friar devised an ideal city plan included in his works Lo Crestià and Regiment de la cosa pública (1383), considered a valuable model apt to guide urban government and arguably town planning. Such an issue is examined in this paper in the context of Eiximenis observations and criticism on architecture and built environments: if some of his ideas constitute a blend of several ancient and medieval authors, others do reflect personal experience or updated knowledge of building practices and the social use of architecture in late medieval Europe.